ISO 22000 standard implementation: Benefits, motivations and obstacles - Gonçalves, J. (2020)
Purpose - The aim of this paper is to evaluate benefits, motivations, and obstacles of the implementation of ISO 22000 in the food industry and do a comparative relation in multiple countries. The study identifies the main difficulties faced by companies during the adoption process and the benefits found on their overall satisfaction with ISO 22000. Design/methodology/approach - A research was performed to identify the existence of studies about difficulties and benefits of ISO 22000 implementation. The literature review resulted in the selection of studies about the Food Safety Management System (FSMS) in different countries, with special focus on ISO 2200 implications. Findings - There are several benefits that companies can obtain from having an implemented and certified FSMS. It is possible to observe similar benefits when ISO 22000 is implemented. The difficulties to the implementation of ISO 2200 were identified by all companies, however they demonstrated to be pleased with the benefits (internal and external) of the certification. Research limitations A small percentage of papers were found about the ISO 22000 implementation. Most case studies focus on Food Safety without a specific focus on ISO 22000. Originality/value - The studied papers comprised certified companies and analyzed benefits and obstacles of the implementation of ISO 22000, including representatives of all links in the Food Chain.